Detection of a Sudan dye at low concentrations by surface-enhanced Raman spectroscopy using silver nanoparticles - Dao, Tran Cao; Luong, Truc Quynh Ngan; Cao, Tuan Anh; Kieu, Ngoc Minh (Communications in Physics, 2019)
Sudan dyes are red colorants banned from use for food due to their toxic properties. However, because of the cheapness, they are sometimes adulterated into food illegally. Currently surface-enhanced Raman spectroscopy (SERS) is emerging as a good method to detect residues (including trace amounts) of Sudan dyes in food. In this report we present the SERS detection of Sudan I (a type of Sudan dyes) to concentrations as low as 1 ppb, using a very simple SERS substrate, which is made from silver nanoparticles chemically deposited on silicon surface.